The Community Structure of Sea Urchin (Echinoidea) in Seagrass Ecosystem at Batu Jimbar Beach Sanur Denpasar - Sang Ayu Made Putri Suryani; Rosito Da Costa Freitas; I Made Kawan (Warmadewa University Press, 2022)
Abstract This study aims to determine the intensiveness of sea urchins (Echinoidea) and the community structure of sea urchins in the seagrass ecosystem at Batu Jimbar beach, Sanur, Bali Province. In this study, the stations were determined based on the distribution and cover of seagrass so that there were three stations, namely station I located at the coordinates 115 ° 15'58.17